Ethnobotanical Studies and Biological Screening of Tinospora cordifolia - Modi, Bindu; Timilsina, Hari; Basnyat, Ram Chandra (Our Nature, 2019)
The aim of this study was to carry out the ethno-botanical survey to determine the importance of traditional medicinal Tinospora cordifolia plant and to evaluate phytochemical screening and anti-oxidant potential of plant extract of Tinospora cordifolia. Traditionally, it is used alone or with other medicinal plants to treat common disease such as fever, diabetics, urinary tract infection and piles problem. Phytochemical screening proved that plant extracts are the rich sources of secondary metabolites such as alkaloids, glycosides, flavonoids, terpenoids etc. Antioxidant activity of these plant extracts was studied by DPPH radical scavenging assay which proved the inhibitory concentration, IC50 value of hexane and methanol extract of leaves of Tinospora cordifolia were 140 and 79.41 µg/ml and hexane and methanol extract of stem were found to be 126.52 and 76.26 µg/ml, Similarly IC50 value of methanol extract of leaves and stem from percolation method were 94.83 and 91.88 µg/ml . The IC50 value thus provided scientific information that T. cordifolia can be used as a potential candidate in different pharmaceutical purpose.